The Efforts of Akidah Akhlak Teachers in Shaping Students’ Religious Behavior at MTS Al-Munawaroh Tabir Raya - Irdawati; Ely Surayya (Lembaga Bale Literasi, 2025)
This study aims to describe the efforts of Akidah Akhlak teachers in shaping students' religious behavior at MTs Al-Munawaroh Tabir Raya. The study employed a qualitative descriptive approach with data collected through observation, in-depth interviews, and documentation. Research informants consisted of an Akidah Akhlak teacher, the school principal, and eighth-grade students selected through purposive sampling. Data analysis followed the interactive model proposed by Miles, Huberman, and Saldaña, comprising data reduction, data display, and conclusion drawing. The findings reveal that Akidah Akhlak teachers implement three principal strategies in shaping students' religious behavior, namely role modeling (uswah hasanah), systematic religious habituation including Qur'anic recitation and congregational prayers, and the deliberate integration of moral values throughout the instructional process. Behavioral evaluation is conducted formatively through continuous observation and personalized guidance. These three strategies operate synergistically and mutually reinforce one another. The study concludes that effective religious character formation requires a holistic approach that simultaneously integrates the instructional, exemplary, and institutional religious culture dimensions in a sustained and coherent manner.